The capacity of the natural person: An analysis of the Civil Code according to the General Law of Disability: A change of visión of the Civil Right for the Human Rights - Roca Mendoza, Oreste Gherson (2015)
This essay is about the analysis of the capacity establishment of natural persons through the Civil Code, its change of the traditional model to the social one to establish the equality between the persons who are disabled and the ones who are not, according to the international and national standards, starting by the definition of the legal personality, the current regulation of incapacity that is applied to persons who suffer from it or from physical and/or mental impairment, the invalidity of their acts, the curatorship, and interdiction, and its contrast to the social model developed by both, the conventions of human rights and the Law No. 29973, General Law of Disability, and the international and national jurisprudence level, in order to alert its failure and its needed modification, which has been carried out by the Special Committee of Inspection of the Civil Code (CEDIS), for the implementation of the support system.